Purification and Molecular Characterization of the Tungsten-Containing Formaldehyde Ferredoxin Oxidoreductase from the Hyperthermophilic Archaeon Pyrococcus furiosus: the Third of a Putative Five-Member Tungstoenzyme Family - Roy, Roopali (American Society for Microbiology, 1999)
Pyrococcus furiosus is a hyperthermophilic archaeon which grows optimally near 100°C by fermenting peptides and sugars to produce organic acids, CO(2), and H(2). Its growth requires tungsten, and two different tungsten-containing enzymes, aldehyde ferredoxin oxidoreductase (AOR) and glyceraldehyde-3-phosphate ferredoxin oxidoreductase (GAPOR), have been previously purified from P. furiosus. These two enzymes are thought to function in the metabolism of peptides and carbohydrates, respectively. A third type of tungsten-containing enzyme, formaldehyde ferredoxin oxidoreductase (FOR), has now been characterized. FOR is a homotetramer with a mass of 280 kDa and contains approximately 1 W atom, 4 Fe atoms, and 1 Ca atom per subunit, together with a pterin cofactor. The low recovery of FOR activity during purification was attributed to loss of sulfide, since the purified enzyme was activated up to fivefold by treatment with sulfide (HS(−)) under reducing conditions. FOR uses P. furiosus ferredoxin as an electron acceptor (K(m) = 100 μM) and oxidizes a range of aldehydes. Formaldehyde (K(m) = 15 mM for the sulfide-activated enzyme) was used in routine assays, but the physiological substrate is thought to be an aliphatic C(5) semi- or dialdehyde, e.g., glutaric dialdehyde (K(m) = 1 mM). Based on its amino-terminal sequence, the gene encoding FOR (for) was identified in the genomic database, together with those encoding AOR and GAPOR. The amino acid sequence of FOR corresponded to a mass of 68.7 kDa and is highly similar to those of the subunits of AOR (61% similarity and 40% identity) and GAPOR (50% similarity and 23% identity). The three genes are not linked on the P. furiosus chromosome. Two additional (and nonlinked) genes (termed wor4 and wor5) that encode putative tungstoenzymes with 57% (WOR4) and 56% (WOR5) sequence similarity to FOR were also identified. Based on sequence motif similarities with FOR, both WOR4 and WOR5 are also proposed to contain a tungstobispterin site and one [4Fe-4S] cluster per subunit.